Model of Tourist Destination in Cibuntu Village, West Java - Hidayat, Candra; Arafah, Willy; Rahmanita, Myrza; Gantina, Devita; Boediman, Surya Fadjar (Institut Pariwisata dan Bisnis Internasional, 2022)
A6 model consist the attributes of tourist destination that are attraction, accessibility, amenities, available package, activities, and ancillary service. They both have an influence on increasing tourist satisfaction. Health protocol is also the perception to enhance tourist satisfaction in new normal. Consequently, health protocol plays an important role in boosting the tourist satisfaction in Cibuntu Village, West Java. This study analyses the relationships proposed in SERVQUAL, which consist five core components of service quality: tangibles, reliability, responsiveness, assurance and empathy. The sample in this study was 200 respondents from the tourists who experienced at least one time of visiting Cibuntu Village. This study using questionnaires in the kind of Google form, consists of 23 items.Five hypotheses were formulated and tested. The finding of this study found from all respondents is also going down more than four time experiences. Then offer a promotion for the young generation or under 25 year old market segment. In the new normal, the application of health protocols determines tourist satisfaction in Cibuntu Village, West Java. The process of building, designing, and defining a sustainable tourism village, we must collaborate with the central government and local government in the new normal situation. Cibuntu Village should collect the data from the tourist visiting Cibuntu village and save it as guest history to offer a suitable promotion in new normal.